Phytochemical screening and antibacterial activity of medicinal plants used to treat typhoid fever in Bamboutos division, West Cameroon - Tsobou Roger, Mapongmetsem Pierre-Marie, Voukeng Kenfack Igor, Van Damme Patrick (Journal of Applied Pharmaceutical Science, 2015)
This study was undertaken to document how typhoid is traditionally treated in Bamboutos division. For this purpose thirty eight plants species were selected. These plants underwent phytochemical screening and antibacterial study using standard procedures. The antibacterial tests using agar well diffusion method and microdilution assay indicated that, all the thirty eight plant samples showed activity against S. typhi, while S. paratyphi A and S. paratyphi B reacted on fifteen and fourteen plants respectively. The highest zones of inhibition were obtained from Senna alata with diameter of 24, 22.5 and 20.5 mm against S. paratyphi A, S. paratyphi B and S. typhi respectively at 160 mg/ml concentration. The lowest MIC values 128 µg/ml was exhibited by the extract of Vitex doniana against Salmonella paratyphi A. Bactericidal activity was obtained by the extract of Carica papaya, Pseudarthria confertiflora, Moringa oleifera and Harungana madagascariensis. Antibacterial screened of Pseudartthria confertiflora was reported for the first time. Annona muricata, Laggera alata, Spathodea campanulata, Cordia platythyrsa, Carica papaya, Terminalia glaucescens and Pseudarthria confertiflora gave positive results for all secondary metabolites while other plants contained two to five metabolites. The presence of these secondary metabolites probably contributes to the antibacterial potential of these plants. This finding supported the uses of these plants for treatment of typhoid fever and other infectious diseases in the study area.
Keywords: Phytochemical screening, antimicrobial, typhoid fever, medicinal plants, MIC, bactericidal.